Revision of the genus Adelostoma (Coleoptera: Tenebrionidae). Part 2: A new subgenus and species from Oman - Purchart, Luboš (Zootaxa, 2017)
A new species Adelostoma muqalensis sp. nov. is described from Oman, figured and compared with its relatives. The new species is placed in a new monotypic subgenus, Omandelostoma subgen. nov. An identification key for subgenera of the genus Adelostoma is given.